Knowledge and Attitudes Toward Human Papillomavirus Vaccination Among Latina Mothers of South American and Caribbean Descent in the Eastern US - Rula Btoush; Diane R. Brown; Jennifer Tsui; Lindsey Toler; Jennifer Bucalo (Mary Ann Liebert, 2019)
Purpose: The purpose of this study was to examine knowledge, attitudes, barriers, and facilitators for human papillomavirus (HPV) vaccination among Latina mothers of HPV vaccine-eligible children in low-income urban areas, as well as useful strategies to improve HPV vaccination. Methods: The study included 132 Latina mothers of HPV vaccine-eligible children, interviewed in 14 focus groups. Using semi-structured discussions, mothers were asked about their knowledge about HPV infection and vaccine, views toward HPV vaccination, barriers for HPV vaccine initiation as well as completion, and opinions on strategies to improve HPV vaccination. Results: Only 55% of mothers reported having ever heard of the HPV vaccine, 27% of mothers indicated initiating the HPV vaccine, and 14% indicated completing the multi-dose series. Mothers generally lacked knowledge about HPV infection and vaccination, with varying degrees by Latino descent. Health care provider (HCP) recommendation was the strongest barrier/facilitator for HPV vaccination. Useful strategies to improve HPV vaccine initiation and completion that the mothers suggested included strong recommendation from HCPs and addressing side effects and safety concerns. Other useful strategies included community and school-based approaches and the use of text messaging and smartphone technology to educate mothers and send vaccine reminders. Conclusion: The findings provide insight for the development of interventions targeting low-income Latina mothers and the need to improve HCP communication on HPV vaccination.